2022
DOI: 10.3389/fphar.2022.1045465
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline attenuates l-DOPA-induced dyskinesia through an anti-inflammatory effect in a hemiparkinsonian mouse model

Abstract: The pharmacological manipulation of neuroinflammation appears to be a promising strategy to alleviate l-DOPA-induced dyskinesia (LID) in Parkinson’s disease (PD). Doxycycline (Doxy), a semisynthetic brain-penetrant tetracycline antibiotic having interesting anti-inflammatory properties, we addressed the possibility that this compound could resolve LID in l-DOPA-treated C57BL/6 mice presenting either moderate or intermediate lesions of the mesostriatal dopaminergic pathway generated by intrastriatal injections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…In a recent study by Dos Santos Pereira et al (2022) [ 272 ] Doxy affected L-DOPA-induced dyskinesia (LID) in mice with dopaminergic impairment induced by intrastriatal injection of 6OHDA. In this model, Doxy given before L-Dopa significantly attenuated LID, and the effect was associated with a reduction in inflammatory markers in the striatum.…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…In a recent study by Dos Santos Pereira et al (2022) [ 272 ] Doxy affected L-DOPA-induced dyskinesia (LID) in mice with dopaminergic impairment induced by intrastriatal injection of 6OHDA. In this model, Doxy given before L-Dopa significantly attenuated LID, and the effect was associated with a reduction in inflammatory markers in the striatum.…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…Vancomycin pre-treatment in an MPTP mouse model of PD was found to improve motor function potentially through microbiota alterations and the suppression of inflammation ( 55 ) and a similar mechanism may be in play here. Doxycycline followed by LD treatment of a 6-OHDA PD mouse model resulted in reduced L-DOPA-induced dyskinesia—without affecting LD-induced motor improvements—potentially by suppressing inflammation ( 56 ). Although our study used a different antibiotic treatment and PD mouse model, we also observed a reduction in TNF-alpha expression, as well as some mild motor improvements, due to Abx treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As described above, treatment with MPEP (a metabotropic glutamate receptor 5 antagonist) reduced the onset of LIDs in de novo MPTP-lesioned monkeys through decrease of inflammatory reaction by means of IBA1, GFAP, and CD68 in the basal ganglia without effects in the nucleus accumbens and motor cortex M1 [88]. An alternative treatment for LIDs in PD could be the use of doxycycline (doxy), a semisynthetic tetracycline antibiotic with anti-inflammatory characteristics able to pass the BBB [124]. Doxycycline triggered the reduction of LIDs in L-DOPA-treated dyskinetic mice by decreasing Fos-B and COX-2 expression and lowering PGE 2 , TNF-α, and IL-1β levels in the dorsolateral striatum [124,125].…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…An alternative treatment for LIDs in PD could be the use of doxycycline (doxy), a semisynthetic tetracycline antibiotic with anti-inflammatory characteristics able to pass the BBB [124]. Doxycycline triggered the reduction of LIDs in L-DOPA-treated dyskinetic mice by decreasing Fos-B and COX-2 expression and lowering PGE 2 , TNF-α, and IL-1β levels in the dorsolateral striatum [124,125].…”
Section: Therapeutic Interventionsmentioning
confidence: 99%